2016
DOI: 10.1111/ajo.12462
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of thyroid dysfunction and thyroid antibodies in a private obstetrical practice in Sydney

Abstract: A high prevalence of subclinical hypothyroidism and positive thyroid antibodies exists in this cohort, as well as unsuspected chemical hypothyroidism, providing a strong case for universal screening with TSH and the consideration of thyroid antibody testing of all Australian pregnant women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
(47 reference statements)
0
12
0
Order By: Relevance
“…Furthermore, we need to consider the effect of autoimmunity on thyroid function because 16% of pregnant women with eTSH had TSH antibodies according to our study. The prevalence of positive thyroid antibodies is low compared to that of Australian pregnant women with SCH (41-67%) (Blumenthal et al 2016). Consequently, SCH in Japan might be caused by iodine excess.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Furthermore, we need to consider the effect of autoimmunity on thyroid function because 16% of pregnant women with eTSH had TSH antibodies according to our study. The prevalence of positive thyroid antibodies is low compared to that of Australian pregnant women with SCH (41-67%) (Blumenthal et al 2016). Consequently, SCH in Japan might be caused by iodine excess.…”
Section: Discussionmentioning
confidence: 90%
“…iodine deficiency with a high prevalence of thyroid autoimmunity (Stagnaro-Green et al 1990;Andersson et al 2012;Blumenthal et al 2016). The synergistic effect of iodine deficiency and autoimmunity may have a substantial influence on maternal and fetal outcome.…”
Section: Discussionmentioning
confidence: 99%
“…To sum up, in previous studies, autoimmunity and iodine intake were claimed to be the main underlying mechanisms for adverse pregnancy outcomes . In studies that were performed in China and Japan, antibody positivity and iodine excess were found to be main reasons, whereas the main cause in overseas is reported to be iodine deficiency and high prevalence of antibodies . In our country, it was shown that even with salt iodinization in pregnancy, pregnancies are prone to be faced with some degree of iodine deficiency .…”
Section: Discussionmentioning
confidence: 75%
“…If prospective trials find that treating subclinical hypothyroidism in pregnancy is beneficial, this would support universal screening in future. 22 …”
Section: Antithyroid Therapymentioning
confidence: 99%